Transformation of the labor market and the necessary professional competencies of employees under the influence of the development of technologies and practical sciences (Nexo Revista Científica, 2022)
With the transformation of technologies, the requirements for labor resources are also being modified, for which it will be necessary to adapt to the latest circumstances and trends in the labor market in the short term. Therefore, it is important to have work skills and competencies that are practically significant and relevant for a potential employer. The sectoral nature of the economy, technologies implemented by companies and technical production equipment set the tone for the professional structure of personnel and the demand for labor resources, considering professional competencies. According to experts, to adapt and respond to uninterrupted technological progress in the future, people will alternately master about 10 professions throughout their lives. Today, as in the last 5-7 years, the demand for IT specialists is actively developing, to a greater extent for system and computer developers and analysts, and security experts. Modern employers point out that development skills along with easy learning new things are the priority qualities of potential employees. In addition: the ability to correctly respond to the introduced technological changes; communication skills not only within a single specialty, but also far beyond its framework; processing the large information volumes. The priority competencies of personnel are closely linked to the technological space and economic digitalization of Russia.